Arrangement of Tourist Attraction Objects and Development of the Kompos Hill Tourism Village in Bolang Village, Dayeuhluhur District, Cilacap Regency, Central Java - Sugara, Sugara; Tauhid, Rijal; Missalam, Talam; Fadlur Rohman, Rivan; Fernanda Badrussalam, Rio Rizky; Ghazali, Puspa Liza; Pratiwi, Anggia Suci; Hendrawan, Budi; Mujiarto, Mujiarto (AbdimasMu UMTAS, 2023)
The development of a tourist village is one of the tourism developments that can introduce the potentials of a village. Good planning must be complemented by a strategy for managing tourist destinations so that it has many positive impacts and minimizes the negative impacts that may occur. This service activity was carried out on the basis of the existence of several problems faced by tourism product tourism village managers in Bolang Village, namely the lack of readiness and commitment of tourism HR as a whole. The main objective of development activities is to accelerate community empowerment and related institutions for the management of tourist villages. Community service activities are carried out using qualitative methods and followed by training to improve skills in designing packaging or tour packages. Tourism development planning in practice must pay attention to the zoning that has been arranged in a good spatial layout. Implementation of tourism village development program activities as an effort to provide an overview of management, arrangement, promotion and publication in Bolang Village. This activity received a good response from the community, village government and social institutions.